High complement levels in astrocyte-derived exosomes of Alzheimer's disease - Goetzl, Edward J. (Ann Neurol, 2018)
OBJECTIVE: Astrocytes fulfill neuronal trophic roles normally, but are transformed in Alzheimer's disease (AD) into A1-type reactive astrocytes that may destroy neurons through unknown mechanisms. METHODS: To investigate astrocyte inflammatory mechanisms, astrocyte-derived exosomes (ADEs) were isolated immunochemically from plasmas of AD patients and matched controls for ELISA quantification of complement proteins. RESULTS: ADE levels of C1q, C4b, C3d, factor B, factor D, Bb, C3b and C5b-C9 terminal complement complex (TCC), but not mannose-binding lectin (MBL), normalized by the CD81 exosome marker were significantly higher for AD patients (n=28) than age- and gender-matched controls (all p<0.0001). ADE normalized levels of IL-6, TNF-α and IL-1β were significantly higher for AD patients than controls, but there was greater overlap between the two groups than for complement proteins. Mean ADE levels of complement proteins for AD patients in a longitudinal study were significantly higher (n=16, p<0.0001) at the AD2 stage of moderate dementia than at the AD1 preclinical stage five to 12 years earlier, which were the same as for controls. ADE levels of complement regulatory proteins CD59, CD46, decay-accelerating factor (DAF) and complement receptor type 1 (CR1), but not factor I, were significantly lower for AD patients than controls (p<0.0001 for CD59 and DAF), were diminished by the AD1 stage and were further decreased at the AD2 stage. INTERPRETATION: ADE complement effector proteins in AD are produced by dysregulated systems, attain higher levels than in controls, and may potentially damage neurons in the late inflammatory phase of AD.